Voluntary Environmental Disclosure by Australian Listed Mineral Mining Companies: An Application of Stakeholder Theory - Christopher, Theo; Hutomo, Sigit; Monroe, Gary (Accounting Department,, 1997)
Within the stakeholder theory framework this paper examines the extent of voluntary environmental disclosure (ED) in relation to characteristics of Australian listed mineral mining ï¬rms. Three indexes, words, unweighted and weighted index, are calculated to measure the association of total ED and categories of total ED with ï¬rm characteristics within the three dimensions of stockholder theory. We ï¬nd that the three indexes for total ED and categories of disclosure are signiï¬cantly associated. Consequently, a single construct is employed as a surrogate for the indexes. The result of Ordinary Least Squares Regression of this construct as a dependent variable with ownership diffusion, ï¬nancial leverage and membership of the Australian Mining Industry Council (AMIC) as proxies for stakeholder power; the presence of a corporate environmental committee as a proxy for strategic posture; retum on equity and systematic risk as proxies for economic performance ; and ï¬rm size and commercial production as control variables showed that membership of AMIC and size were statistically signiï¬cant. The implication of this ï¬nding is that ï¬nancial variables do not explain voluntary ED and that the variables used in the strategic posture and economic performance dimensions of stakeholder theory are not signiï¬cant. This implies, subject to limitations of the study, that the regulators of accounting infonnation will need to issue an accounting standard if they